A Comparative Study Of Figurative And Idiomatic Expressions In English And Uzbek: Insights Into Translation And Cross-Cultural Communication - Mannonova, Mokhinur (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This brief academic paper analyzes the similarities and differences between figurative and idiomatic expressions in English and Uzbek. The study explores the semantic features of idiomatic units, their role within the national mentality, challenges in the translation process, and their significance in cross-cultural communication. Since language is not only a means of communication but also a cultural mirror, translating idioms and figurative expressions requires attention to both linguistic and cultural context. The research examines semantic differences and translation strategies through examples of English and Uzbek idioms.